204. In-silico implementation of Linac MRI based radiotherapy: A dosimetrical comparison with rectal cancer. (December 2018) - Placidi, E.; Teodoli, S; Stimato, G.; Greco, F.; Menna, S.; Placidi, L.; Cusumano, D.; Boldrini, L.; Valentini, V.; Azario, L.; De Spirito, M.
Abstract : Purpose: MR-guided radiotherapy is a new promising technique. Our department is equipped with a MRIdian 60Co system (Viewray) and we are implementing the TPS of the first 6 MV MR-Linac available for clinical practice (ViewRay). The aim of this study is to assess the impact of the MRIdian Linac through a planning analysis for rectal cancer treatments. Methods: Four plans (MRIdian Linac, MRIdian 60Co, RapidArc and sliding windows IMRT) were calculated for 10 patients affected by rectal cancer. ROIs were contoured on Eclipse TPS (version 11.0, Varian). The body, the bowel bag and the bladder were the OaR considered. The prescribed dose for PTV2 was 45 Gy and 55 Gy for PTV1 through SIB. RapidArc (6–15 MV) and 5 beams (6–15 MV) sliding windows IMRT treatment plans were calculated on Eclipse using the Analytical Anisotropic Algorithm. 60Co step and shoot IMRT and 7 beams 6 MV step and shoot IMRT were perfomed with the MRIdian systems, equipped with a GPU-accelerated Monte Carlo Algorithm. The PTV V95 and OaRs QUANTEC dose constraints on the DVHs were considered for the QA of the plans. Results: Both MRIdian 60Co and MRIdian Linac showed a better PTV1 coverage. Comparable mean doses for the bladder were registered, while a higher bowel V45 was observed for MRIdian 60Co. Low dose body V5 was higher for the MRIdian 60Co plans whilst the MRIdian Linac low doses resulted to be comparable to the conventional Linac. Conclusions: MRIdian allowed reaching dosimetrical goals comparable to RapidArc and IMRT gold standards. The MRIdian Linac resulted in smaller low doses distribution, comparable to the conventional IMRT technique. The availability of an on-board MR imaging system might lead to the reduction of the target margin. This aspect will be investigated when the system will become operative.